Cascading Cache Layer in Content Management System - Ganapathy, Apoorva (Asian Business Review, 2018)
Caching involves the temporal storing of data in a separate folder. Cascading is the arrangement of something in sequence from top to bottom. Cascading cache layer in content management system places data in layers and sequence in order of importance. The cached data are also removed based on their order of importance. Caching is majorly about input and output of content and data, this brings the need for cascading management system to make accessing data easier than usual. This work takes a look into caching and how it works. It considers various levels of caching in the content management systems. It tries to explain what cascading is in a content management system as well as its importance. This work explains how cascading cache in layers would make it faster and more efficient to access data.